Scoping the impact of the national child measurement programme feedback on the child obesity pathway: study protocol - Falconer Catherine; Park MinHae; Skow Áine; Black James; Sovio Ulla; Saxena Sonia; Kessel Anthony; Croker Helen; Morris Steve; Viner Russell; Kinra Sanjay (BMC, 2012)
Abstract Background The National Child Measurement Programme was established to measure the height and weight of children at primary school in England and provides parents with feedback about their child's weight status. In this study we will evaluate the impact of the National Child Measurement Programme feedback on parental risk perceptions of overweight, lifestyle behaviour and health service use. Methods The study will be a prospective cohort study of parents of children enrolled in the National Child Measurement Programme and key service providers from 5 primary care trusts (administrative bodies responsible for providing primary and secondary care services). We will conduct baseline questionnaires, followed by provision of weight feedback and 3 follow up questionnaires over the course of a year. Questionnaires will measure change in parental risk perception of overweight, health behaviours and health service use. Qualitative interviews will be used to identify barriers and facilitators to change. This study will produce preliminary data on National Health Service costs associated with weight feedback and determine which feedback approach (letter and letter plus telephone) is more effective. Discussion This study will provide the first large scale evaluation of the National Child Measurement Programme feedback. Findings from this evaluation will inform future planning of the National Child Measurement Programme.